Closed-form solutions for accelerated MHD flow of a generalized Burgers’ fluid in a rotating frame and porous medium - Khan, Ilyas (Springer International Publishing, 2015)
Closed-form solutions for magnetohydrodynamic (MHD) and rotating flow of generalized Burgers’ fluid past an accelerated plate embedded in a porous medium are obtained using the Laplace transform technique. Modified Darcy’s law for generalized Burgers’ fluid is taken into account. Both constant and variable acceleration cases are considered. The graphical results along with illustrations are presented to bring out the effects of indispensable parameters on the velocity. The obtained solutions are reduced as special cases to their limiting solutions by taking some suitable parameters equal to zero.